Intestinal Barrier Function in Chronic Kidney Disease - Björn Meijers; Ricard Farré; Sander Dejongh; Maria Vicario; Pieter Evenepoel (Toxins, 2018)
The kidneys are key contributors to body homeostasis, by virtue of controlled excretion of excessive fluid, electrolytes, and toxic waste products. The syndrome of uremia equals the altered physiology due to irreversible loss of kidney function that is left uncorrected for, despite therapeutic intervention(s). The intestines and its microbial content are prime contributors to this syndrome. The intestinal barrier separates the self (or the so-called “milieu intérior”) from the environment. In the large intestine, the intestinal barrier keeps apart human physiology and the microbiota. The enterocytes and the extracellular mucin layer functions form a complex multilayered structure, facilitating complex bidirectional metabolic and immunological crosstalk. The current review focuses on the intestinal barrier in chronic kidney disease (CKD). Loss of kidney function results in structural and functional alterations of the intestinal barrier, contribution to the syndrome of uremia.